Extrapolating continuous color emotions through deep learning - Ram, Vishaal; Schaposnik, Laura P.; Konstantinou, Nikos; Volkan, Eliz; Papadatou-Pastou, Marietta; Manav, Banu; Jonauskaite, Domicele; Mohr, Christine (My University, 2020)
By means of an experimental dataset, we use deep learning to implement an RGB extrapolation of emotions associated to color, and do a mathematical study of the results obtained through this neural network. In particular, we see that males typically associate a given emotion with darker colors while females with brighter colors. A similar trend was observed with older people and associations to lighter colors. Moreover, through our classification matrix, we identify which colors have weak associations to emotions and which colors are typically confused with other colors.
Keywords: Deep learning; Quantitative Biology; Quantitative Methods; Computer Science; Biological Physics; Physics; Neural network